2009
DOI: 10.1021/la804215v
|View full text |Cite
|
Sign up to set email alerts
|

Effective Stabilization of Curcumin by Association to Plasma Proteins: Human Serum Albumin and Fibrinogen

Abstract: The use of curcumin as an effective wound healing agent is of significant interest currently. It is well established that curcumin undergoes rapid degradation in physiological buffer by hydrolysis. The means by which curcumin is stabilized at the wound site to enable healing is poorly understood because blood plasma is composed of approximately 92% water. Plasma proteins, which constitute the remaining 6-8%, has been shown to stabilize curcumin. It is, however, still unclear which proteins are responsible for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
153
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(176 citation statements)
references
References 36 publications
(66 reference statements)
20
153
2
1
Order By: Relevance
“…However, for Cur NPs, there were no obvious reductions to be observed under the same conditions. Similar results have been reported by Leung and Kee (2009), where the authors claimed that under the neutral pH condition Cur could degrade by about 90 % within 30 min at room temperature. In ambient conditions, the Cur NPs in CPH and NaCas were still very stable in 6 h storage compared with the free Cur in PBS (Fig.…”
Section: The Chemical Stability Of Cur Npssupporting
confidence: 89%
“…However, for Cur NPs, there were no obvious reductions to be observed under the same conditions. Similar results have been reported by Leung and Kee (2009), where the authors claimed that under the neutral pH condition Cur could degrade by about 90 % within 30 min at room temperature. In ambient conditions, the Cur NPs in CPH and NaCas were still very stable in 6 h storage compared with the free Cur in PBS (Fig.…”
Section: The Chemical Stability Of Cur Npssupporting
confidence: 89%
“…It has been reported that the stability of curcumin increases when bound to plasma proteins or loaded in nanoformulations (39)(40)(41). We therefore studied the degradation of curcumin in two different formulations, namely loaded in mPEG-HPMA-Bz micelles and in Triton X-100 micelles.…”
Section: Degradation Of Curcumin (As Curcuminoid Mixture) Loaded In Mmentioning
confidence: 99%
“…Because of the low aqueous solubility, curcumin tends to aggregate and precipitate in water, limiting its bioavailability. [13][14][15][16] In addition, curcumin undergoes rapid degradation in water and buffer solutions, with a reaction half-life of 9.5 min at pH 7.2. 17 It has been demonstrated that the degradation is mostly due to deprotonation of curcumin, producing the degradation products vanilin, ferulic acid, and feruroyl methane.…”
Section: Introductionmentioning
confidence: 99%